2020
DOI: 10.1016/j.energy.2020.117817
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing energy system modelling of decentralized energy autonomy

Abstract: Research attention on decentralized autonomous energy systems has increased exponentially in the past three decades, as demonstrated by the absolute number of publications and the share of these studies in the corpus of energy system modelling literature. This paper shows the status quo and future modelling needs for research on local autonomous energy systems. A total of 359 studies are roughly investigated, of which a subset of 123 in detail. The studies are assessed with respect to the characteristics of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 345 publications
(313 reference statements)
0
41
0
2
Order By: Relevance
“…Modeling by Imelda et al concluded that a 100% renewable system satisfying Hawai'i's 100% RPS law is "surprisingly affordable" and improves welfare in comparison to a fossil fuel-based system even without considering the cost of pollution [104]. Microgrids do not appear to play a substantial role in these works, although related concepts have been reviewed in the context of 100% renewables, such as Eras-Almeida and Egido-Aguilera's review of renewable island mini-grids and Weinand et al's review of decentralized autonomous energy systems [114,115].…”
Section: Hawai'imentioning
confidence: 99%
“…Modeling by Imelda et al concluded that a 100% renewable system satisfying Hawai'i's 100% RPS law is "surprisingly affordable" and improves welfare in comparison to a fossil fuel-based system even without considering the cost of pollution [104]. Microgrids do not appear to play a substantial role in these works, although related concepts have been reviewed in the context of 100% renewables, such as Eras-Almeida and Egido-Aguilera's review of renewable island mini-grids and Weinand et al's review of decentralized autonomous energy systems [114,115].…”
Section: Hawai'imentioning
confidence: 99%
“…Additionally, there are different studies of energy system modeling available handling the general availability of bioenergy as a renewable energy source in scenario development for energy systems in the future. Different reviews regarding the latter have been published, for example, modeling decentralized energy autonomy [48], urban regions [49,50], or on a smaller scale for municipalities [51,52]. These studies state the general availability of bioenergy for renewable energy systems.…”
Section: Energy System Modelingmentioning
confidence: 99%
“…Local authorities and actors such as municipalities and city planners are increasingly incorporating energy planning aspects into their practices [11,12]. This is underlined by the growing body of research and literature on the decentralisation of energy planning, stressing the role of municipalities and challenges faced by municipalities in the transition to renewable energy systems [13,14].…”
Section: Introductionmentioning
confidence: 99%